EFFECTIVENESS OF NITROGEN-CONTAINING BISPHOSPHONATES IN THE REGULATION OF MINERAL METABOLISM DISTURBANCES ASSOCIATED WITH ALIMENTARY OSTEOPOROSIS IN RATS - Komisarenko S. V.; Volochnyuk D. M.; Shymanskyy I. O.; Ivonin S. P.; Veliky M. M.1 (Biotechnologia Acta, 2015)
The aim of the study was to investigate the effectiveness of nitrogen-containing bisphosphonates synthesized as promising substances for correction of mineral metabolism in osteoporosis. The study was carried out on a model of alimentary osteoporosis that was characterized by hypocalcaemia, hypophosphatemia, decreased 25-Hydroxyvitamin D3 content in blood serum and severe bone tissue demineralization (reduced ash content and mineral components). It was found that synthesized novel nitrogen bisphosphonates (pyrazole-containing analogues), like reference drugs — metylene bisphosphonate (disodium salt of metylene bisphosphonic acid) and alendronate (4-amino-1-hidroxybutyliden bisphosphonate), inhibit with the different efficiency demineralization of the bone tissue and increase the mineral metabolism in rats with alimentary (nutritional) osteoporosis that was assessed by the marker parameters of bone formation. In particular, drug administration (bisphosphonates І-12, І-40, І-42) resulted in elevation of calcium and phosphate levels and decreased the total activity of alkaline phosphatase and its isoenzymes in blood serum. The ash content and the levels of calcium and phosphorus in the ash of tibia and femur bones were shown to be markedly elevated. Bisphosphonate І-12 has shown more profound antiresorbtive activity and ability to correct mineral metabolism in alimentary osteoporosis, including such of reference drugs. It was found a significant decrease of 25-Hydroxyvitamin D3 content in the serum that is considered as a profound vitamin D3 deficiency associated with nutritional osteoporosis. As it was not compensated by bisphosphonates, we suggest that further investigations should be directed to the combined use of both: bisphosphonates as inhibitors of osteoclast activity that diminish bone resorption and vitamin D3 as a key regulator of bone remodeling process and osteosynthesis activator.